Biomimetic Total Synthesis and Investigation of the Non‐Enzymatic Chemistry of Oxazinin A. Issue 38 (16th August 2022) - Aniebok, Victor; Shingare, Rahul D.; Wei‐Lee, Hsiau; Johnstone, Timothy C.; MacMillan, John B.
Abstract: We report the first total synthesis of an antimycobacterial natural product oxazinin A that takes advantage of a multi‐component cascade reaction of anthranilic acid and a precursor polyketide containing an aldehyde. The route utilized for the synthesis of the pseudodimeric oxazinin A validates a previously proposed biosynthetic mechanism, invoking a non‐enzymatic pathway to the complex molecule. We found a 76 : 10 : 9 : 5 ratio of oxazinin diastereomers from the synthetic cascade, which is an identical match to that found in the fermentation media from the fungus Eurotiomycetes 110162. Further investigation of the non‐enzymatic formation of oxazinin A using 1 H‐ 15 N HMBC NMR spectroscopy allowed for a plausible determination of the stepwise mechanism. The developed route is highly amenable for the synthesis of diverse sets of analogs around the oxazinin scaffold to study structure–activity relationships (SAR). Abstract : The first biomimetic total synthesis of natural product oxazinin A is reported. A biosynthetic precursor was synthesized and reacted with anthranilic acid to give oxazinin A. Further investigation of the non‐enzymatic formation of oxazinin A using 1 H‐ 15 N HMBC NMR allowed us to monitor the reaction in real time. The synthetic route is amenable for the synthesis of diverse sets of analogs around the oxazinin scaffold to study the structure–activity relationship.